Response of surface processes to the Holocene landscape changes in Sonora: evidences from the paleosol-sedimentary sequences at the archaeological sites El Fin del Mundo and El Gramal. (December 2020) - Ibarra-Arzave, Georgina; Solleiro-Rebolledo, Elizabeth; Sanchez, Guadalupe; Sedov, Sergey; Golyeva, Alexandra; Morales, Ismael Sanchez; Carpenter, John; Chávez-Vergara, Bruno
Abstract: Northern Mexico is predominantly composed of moderately developed red soils that provide evidence of weathering, rubification, neoformation of clay, and pedogenic carbonate accumulation. These soils constitute a pedological unit named San Rafael Paleosol (SRP) which were developed during the late Pleistocene (MIS 2) to the middle Holocene (15, 000–4500 cal years BP). These paleosols can use as a chronologic marker at a regional scale. In this paper, we present a pedogenic interpretation of the paleosol-sedimentary processes during the late Quaternary, which contributes to the reconstruction of regional paleoenvironment. The development of SRP takes place over more than 15, 000 years, and this pedogenesis is interrupted by stages of strong climatic instability, causing erosion of the SRP and sedimentation, presumably during the Altithermal. The records of La Playa show that SRP is buried by fluvial sediments, which include different facies. These sedimentation events are associated with the end of the Altithermal period and evidence more active geomorphic processes. These conditions are also observed at El Gramal, where dune sediments overly the SRP. This discontinuity evidence an intense erosional/sedimentation phase. In the particular case of El Fin del Mundo site, it is observed more mesic conditions as the water table rose, creating a wetland. Much of the synchronous variation in the morphology of the paleosols (pedofacies) can be explained by differences in local geomorphological conditions. These palaoesols developed under a semi-arid climate, slightly more humid than the present one with winter dominant rains and marked seasonal changes. These assumptions are supported by soil micromorphology, physical characteristics (color, grain size distribution) and composition of total organic and inorganic carbon. Additional paleoenvironmental information is also extracted from microbiomorphic analyses and diatoms assemblages from the one profile at El Fin del Mundo site.